Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2008
DOI: 10.1145/1357054.1357288
|View full text |Cite
|
Sign up to set email alerts
|

On the benefits of confidence visualization in speech recognition

Abstract: In a typical speech dictation interface, the recognizer's bestguess is displayed as normal, unannotated text. This ignores potentially useful information about the recognizer's confidence in its recognition hypothesis. Using a confidence measure (which itself may sometimes be inaccurate), we investigated providing visual feedback about low-confidence portions of the recognition using shaded, red underlining. An evaluation showed, compared to a baseline without underlining, underlining lowconfidence areas did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…It was difficult for them to assess whether the information was to be trusted. The same difficulties have been observed in [13], in an experiment in which hearing people dictated a text and then had to detect the errors made by the speech recognition.…”
Section: Discussionsupporting
confidence: 60%
“…It was difficult for them to assess whether the information was to be trusted. The same difficulties have been observed in [13], in an experiment in which hearing people dictated a text and then had to detect the errors made by the speech recognition.…”
Section: Discussionsupporting
confidence: 60%
“…In conclusion, until confidence scores are more accurate they are unlikely to aid users. We have shown that if confidence scores are accurate enough they do indeed benefit users (Vertanen and Kristensson 2008). However, to reach such levels it may be necessary to incorporate external knowledge outside the speech recognizer.…”
Section: Annotating Words Based On Confidencementioning
confidence: 99%
“…Yet there has been speech technology and HCI collaboration since the Starner [13] and Shneiderman [12] reviews, for example [16,15]. Why is none of this more recent work referenced?…”
Section: Speech Technology Is Marginalisedmentioning
confidence: 99%